Feasibility of extracting operating shapes using phase-based motion magnification technique and stereo-photogrammetry. (27th October 2017) - Poozesh, Peyman; Sarrafi, Aral; Mao, Zhu; Avitabile, Peter; Niezrecki, Christopher
Abstract: Optically-based vibration measurements can be used to determine the full-field dynamic response of structures without the need of mounted transducers (e.g. accelerometers, strain gages, and LVDTs) that can add cost, have wiring, power signal transmission issues, and may affect the dynamic characteristics by adding mass or stiffness. The three-dimensional digital image correlation (3D DIC) and three-dimensional point tracking (3DPT) methods based on a stereo-vision system can provide the full-field dynamic displacements of a structure with sub-pixel accuracy. However, stereo-photogrammetry systems are limited by camera resolution and intrinsic noise of the acquired images. Moreover, exciting a structure with only a small amount of energy may result in a subtle mechanical response that is not perceptible by observing the raw data of the conventional optical measurement systems (i.e. 3D DIC and 3DPT). Thus, in order to use the optical-sensing techniques to identify dynamic characteristics of a structure at high frequencies, the signal-to-noise ratio (SNR) in the sequence of images captured with a stereo-vision system needs to be improved. Within this paper, phase-based video magnification in conjunction with the stereo-photogrammetry techniques are used to measure the higher-frequency operating shapes of a cantilever beam and a 2.3-m long Skystream 4.7 wind turbine blade. The phase-based motion estimation method uses complex steerable pyramids to decompose the original sequence of images to amplitude and phase at different spatial resolutions (subsampled images). Motion information is conserved within the phase values which can be filtered in the time domain and amplified to detect the subtle motions. The magnified sequence of images using the motion magnification technique are post-processed using 3D DIC or 3DPT to quantify infinitesimal deformations that are not recognizable using only the traditional stereo-photogrammetry methods. The results obtained within this paper reveal the great potential of motion magnification in conjunction with stereo-photogrammetry techniques in detecting small motions of structures and extracting 3D operating shapes from the optically measured data with low SNR. Compared to traditional stereo-photogrammetry, additional modes of the test structures are obtainable by means of combining the phase based motion magnification and conventional image-sensing techniques (i.e. 3D DIC and 3DPT). The proposed methodology could be used to enhance the established procedure to extract more information about the dynamic characteristics of structures (only once effectively calibrated), compared to existing image-sensing techniques and contact measurement sensors.